Clinical comparison and complete cure rates of terbinafine efficacy in affected onychomycotic toenails. (30th July 2014) - Shemer, A.; Sakka, N.; Baran, R.; Scher, R.; Amichai, B.; Norman, L.; Farhi, R.; Magun, R.; Brazilai, A.; Daniel, R.
Abstract Background Clinical studies regarding complete cure rate of onychomycosis using oral Terbinafine have a very broad range (14–90%) based solely on response to treatment on the big toenail. Objective To evaluate the efficacy of Terbinafine in all affected onychomycotic toenails and, furthermore, to evaluate differences in mycological, clinical and complete cure rate between affected onychomycotic toenails. Patients and methods Inclusion criteria are as follows: distolateralsubungual onychomycotic involvement of the hallux and additional involvement of at least two more toenails of the same foot. Exclusion criteria are as follows: patients with nail traumata and hypersensitivity to Terbinafine. Patients were treated with oral Terbinafine 250 mg/day for 16 weeks. Mycological analysis was performed using direct microscopy and culture. Clinical improvement was assessed using digital photography. Results Statistically significant difference was found in clinical improvement between the great toenail and all other involved toenails. The rate of complete cure (100% clinical cure and mycological cure) of the big toenail was lower (23%) as compared to the second (65%), third (51%) and the fourth toenail (67%). Limitations This is a case series study that was based on a single‐centre cohort. Conclusions Our results support findings that efficacy of Terbinafine should be based on all involved onychomycotic toenails; the big toenail is not superior in response compared to other affected toenails.